ANALISIS NILAI TAMBAH INDUSTRI PENGOLAHAN BUBUK KOPI UD AYAM MERAK DI DESA GAROT CUT KECAMATAN INDRAJAYA KABUPATEN PIDIE - Mujiburrahmad Mujiburrahmad (Jurnal Bisnis Tani, 2018)
Research on "Value Added Analysis of Coffee Powder Processing Industry UD AYAM MERAK in Garot Cut Village Indrajaya District Pidie". The purpose of this study are: Analyzing added value of UD Ayam Merak coffee powder processing industry in Garot Cut Village, Indrajaya District, Pidie District. This research was conducted by the Processing Industry of UD Ayam Merak Coffee Powder in Garot Cut Village, Indrajaya Sub-district, Pidie District. The selection of the location of this study is determined purposively, on the basis of the consideration that the location is one of the central areas of UD Ayam Merak coffee powder. The object of research is UD Ayam Merak Coffee Bean Processing Industry. The scope of this study is adjacent to the analysis of added value of UD Ayam Merak coffee powder processing industry in Garot Village, Indrajaya District, Pidie Regency ". Based on the results of research that has been done on Value Added Analysis of Coffee Powder Processing Industry UD Ayam Merak in Garot Cut Village Indrajaya District Pidie then the Processing Industry of UD Ayam Merak coffee powder in Garot Cut Village Indrajaya District Pidie District can provide added value. The added value obtained from the processing of coffee beans to coffee powder is Rp 13,500 per kilogram of coffee beans, with a ratio of 15 percent. The ratio of value added to the value of output of 15 percent, indicating that every Rp 100 the value of the output of coffee powder, will be added value of Rp 15. Profits obtained by the business powder based on the calculation of added value is Rp 8,500, with the share of profits obtained is 13.7 percent